PREVALENCE OF ALLERGIC: BRONCHO-PULMONARY ASPERGILLOSIS IN PATIENTS WITH PULMONARY TUBERCULOSIS (Journal of Medical & Health Sciences Review, 2025)
Background: Allergic Bronchopulmonary Aspergillosis (ABPA) is a hypersensitivity airway disease caused by Aspergillus species, and is common in chronic lung disease patients such as Pulmonary Tuberculosis (TB). In TB patients, the immunocompromised state and lung parenchymal loss may predispose to ABPA, which guarantees the exacerbation of the pulmonary condition and complicate the disease.Objective: To determine the prevalence of ABPA in patients with Pulmonary Tuberculosis and assess the impact of co-morbid ABPA on pulmonary-function, disease progression and treatment outcome in patients.Study design: A cross-sectional study.Place and duration of study: From 01 December 2024 to 31 May 2025 Pulmonology Department, Fatima Jinnah Institute of Chest Diseases, Quetta.Methods: A Cross-sectional study was carried out among tuberculosis patients of tertiary care hospital. ABPA was diagnosed on the basis of clinical examination, radiograph and laboratory studies (serum Ige, Aspergillus skin prick test and sputum culture). The prevalence of ABPA was determined and correlated with clinical features, pulmonary findings and clinical response to treatment. Chi-square and p-value calculation were applied in the statistical analysis.Results: A total of 150 patients with pulmonary tuberculosis were included in the study and the median age was 42.3 years (SD ± 12.4). Of these 38 (25.3) patients had ABPA. ABPA was more frequent in patients with cavitary TB (40%) compared with non-cavitary TB (15 percent, p = 0.001). There is a significant reduction in forced expiratory volume (FEV1) in patients with ABPA compared with those without the disease (mean FEV1: 63% -7.4 and 77% -9.2 respectively, p = 0.02). Also, the serum Ige was higher in ABPA-positive patients (mean Ige: 523 IU/mL +- 129.5) than in the non-ABPA group (mean Ige: 175 IU/mL +- 85.6; p < 0.01). Bronchiectasis (p = 0.004) was more common in ABPA patients than in non-ABPA TB patients (60 vs 35, respectively).Conclusion: ABPA is an important co-morbidity of pulmonary tuberculosis with a prevalence of 25.3. Abstract Background: Active Bovine tuberculosis (ABPA) is known to have a negative impact on lung function, especially in those with cavitary TB and high serum IgE and bronchiectasis. It is possible that ABPA can be treated and minimized in its effects on lung health by early diagnosis and treatment of the disease, and may improve overall TB patients' prognosis.